Dental Mandibular Mega-canal: Case Report and Literature Review (Revista Nacional de Odontología, 2017)
Aim: To present a case report on a morphological variation of the mandibular dental canal. Materials and methods: Radiographic evidence of an adult woman from the urban area of Maniza-les-Colombia is provided, exhibiting an increase in size of the dental canal without clinical evidenceof mandibular deformity or symptomatology. This could be associated with a benign tumor due to itsbehavior since it was identified as a radiographic finding in 2013. Results: The biometric studies of the dental canal determine an average diameter of 2.5 mm in normalconditions, which makes us consider this expansion as an alteration of the inferior alveolar nerve. Conclusions: An expansive bone alteration of a mandibular dental mega-canal is reported.
Keywords: biometry; mandibular canal; jaw; neurilemoma